Effect of Magnetized water on the growth of the common carp Cyprinus carpio (L., 1758) - Jabir , Amir A. (Iraqi Journal of Aquaculture, 2023)
Common carp, Cyprinus carpio (L., 1758), fry were used with 0.19 g average weight to estimate the effects of magnetized treated water on fish growth and survival , The experiment was carried out with two treatment and control, 500 fish fi h were randomly distributed at 100 fry fish per replicate per( T1 )and( T2 ) and one replicate for control. Magnetized treated water was used for a period of 24 hours with a magnetized intensity of 1000 gauss in the first treatment, and 1500 gauss in the second treatment. The experiment continued from April to end of June2016. The temperature of the water during the experiment period was ranged 25.9- 27.8 ° C, and oxygen level ranged between (4.8 – 7.1) mg / L. magnetization system was operating 24 hours a day. YSI some environmental factors such as water salinity, pH and water temperature were measured using YSI. Fish were fed twice a day, with 10% of the total weight of fish, with a total protein content of 37%. The gain weight obtained after eight weeks was 1.27±0.049g in (T2), 1.13±0.021g in (T1), while the highest weight in the control treatment reached 0.92±0.007g. The mean of gain weight in the reared fish in (T1) for eight weeks feeding period was 1.10 ± 0.77 g. and in the treatment of 1000 gauss was 0.96 ± 0.67 g, while the mean of gain weight in the control treatment was 0.96 ± 0.53 g. common carp survival rate reared in magnetic water varied under the influence of different magnetic intensities within eight weeks. It was found that the highest survival rate was under the influence of the magnetic intensity of 1500 gauss which was 93%, and the percentage of surviving under magnetic intensity 1000 gauss was 82%, while in the control treatment, it was 45%.